Effect of wave-current interaction on the hydrological environment in a shallow river estuary - Bai, Peng; Chen, Guangji; Wang, Yaofeng; Li, Bo; Ruan, Zhenxin; Gao, Ying (Frontiers in Marine Science, 2025)
Estuarine hydrodynamics, governing the interplay between riverine inputs, tidal currents, and coastal processes, are critical to understanding material transport, ecosystem dynamics, and anthropogenic impacts in transitional coastal zones. This study uses a high-resolution Coupled-Ocean-Atmosphere-Wave-Sediment Transport Modeling System (COAWST) to investigate the wave-current interactions in the shallow Pearl River Estuary during the winter, focusing on two typical tidal phases: maximum flood and maximum ebb. The results indicate that tidal currents significantly modulate the significant wave height, wave direction, and absolute mean bottom period within the estuary, with stronger modulation during maximum ebb. The wave-enhanced bottom friction notably weakens both maximum flood and ebb tidal currents, causes phase delays in the water level, and enhances tidal energy dissipation, which results in a reduction of water level amplitudes, especially at the estuary head. Wave-enhanced mixing and 3D wave forces cause significant adjustments in the current field nearby the plume front. The adjustments in the current field by the wave-enhanced bottom stress restrict more freshwater near the river mouths, lowering the salinity at the estuary head while increasing the salinity south of Qi’ao Island, significantly influencing the location of the plume front. Additionally, wave-enhanced mixing and wave forces significantly influence the position of the plume front. This study provides new insights into the wave-current interactions in the Pearl River Estuary and their impact on the dynamics of the freshwater plume.